Screening and Characterization of Bacteriocin Producing Lactic Acid Bacteria Isolated from Chicken Intestine - Komkhae Pilasombut; Worawidh Wajjwalku; Sunee Nitisinprasert; Adisorn Swetwiwathana; Takeshi Zendo; Jiro Nakayama; Kenji Sonomoto; Thavajchai Sakpuaram (Agriculture and Natural Resources, 2005)
Five hundred strains of lactic acid bacteria (LAB) were isolated from chicken intestine and screened for their abilities to produce bacteriocins. One strain, K4, produced a bacteriocin with activity against Lactobacillus sakei subsp. sakei JCM 1157T, Leuconostoc mesenteroides subsp. mesenteroides JCM 6124T, Bacillus coagulans JCM 2257T, Enterococcus feacalis JCM 5803T, Listeria innocua ATCC 33090T and Brochotrix campestris NBRC 11547T. The antibacterial activity was inactivated by proteolytic enzymes, indicating that it has proteinaceous structure of a bacteriocin. Its properties were heat-tolerance at 121°C for 15 min and stable at wide pH range of 3-10. The mode of action of this bacteriocin was clearly bactericidal activity against Lb. sakei subsp. sakei JCM 1157T and B. coagulans JCM 2257T whereas it showed bacteriostatic action against Br. campestris NBRC 11547T. In addition, K4 strain was able to grow and produce bacteriocin in MRS containing 4% NaCl and at wide pH range of 3-9. Based on morphological, biochemical characteristics and 16S rDNA nucleotide sequence analysis, K4 strain was identified as Lactobacillus salivarius.